EFEKTIVITAS MEDIA PEMBELAJARAN ASSEMBLR EDU BERBASIS AUGMENTED REALITY (AR) DALAM PEMBELAJARAN DIFERENSIASI UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPAS KELAS IV DI MIS THORIQUSSALAM SIDOARJO - Yulfa Fitria, Risda Lailul; M. Amin Hasan; Febriarsita Eka Sasmita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Natural Science Learning (IPAS) is one of the learning processes that requires learning media to achieve learning objectives and solutions to improve learning outcomes, lack of learning motivation, learning facilities in accordance with the learning style of students learning style. This research describes the development of learning media Assemblr edu learning media based on Augmented reality (AR) in differentiation learning to improve students' learning outcomes to improve students' learning outcomes. The purpose of this research is to determine the effectiveness of the development of AR-based assemblr edu learning media AR-based learning media. This type of research uses development research (R&D) with the research model used is the ADDIE model. This model consists of analysis, design, development, implementation, and evaluation. Data collection using validation sheets, observations, and tests. Sheet validation sheet was used to obtain validation data from validators and learner responses response of learners. The observation technique was used to obtain data on the implementation of learning in the classroom, while the test technique was used to obtain data on the learning outcomes of students. Data analysis on the data obtained was carried out through normality test, homogeneity test, paired samples t-test, and N-gain score. In addition, to determine the effectiveness of AR-based learning media development AR-based learning media development was carried out the N-gain Score test. Results The results showed that the augmented reality-based asssemblr edu learning media has fulfilled the research procedures through 5 stages of development reality-based learning media has fulfilled the research procedure through 5 stages of development. The learning media developed by researchers is declared effective as seen from the increase in the average score of 85.18 with the category “effective”. Keywords: Development, Learning Media, IPAS learning outcomes